2019
DOI: 10.3390/foods8100482
|View full text |Cite|
|
Sign up to set email alerts
|

Overall Nutritional and Sensory Profile of Different Species of Australian Wattle Seeds (Acacia spp.): Potential Food Sources in the Arid and Semi-Arid Regions

Abstract: Wattle seed (Acacia spp.) is a well-known staple food within indigenous communities in Australia. A detailed investigation of the overall nutritional and sensory profile of four abundant and underutilized Acacia species—A. coriacea, A. cowleana, A. retinodes and A. sophorae—were performed. Additionally, molecular weight of protein extracts from the wattle seeds (WS) was determined. The seeds are rich in protein (23–27%) and dietary fibre (33–41%). Relatively high fat content was found in A. cowleana (19.3%), A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…In addition, roasting may result in the formation of new compounds or the release of bound compounds such as phenolic and non-phenolic compounds with potential antioxidant properties [ 30 , 31 , 32 ]. Moreover, previous studies have demonstrated that a unique aroma and flavor was perceived in five AS species after roasting [ 8 ] and the aroma and flavor compounds may have been formed or released during roasting. However, the impact of roasting (180 °C) on AS may vary among the AS species due to the differences in their sizes and dimension.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, roasting may result in the formation of new compounds or the release of bound compounds such as phenolic and non-phenolic compounds with potential antioxidant properties [ 30 , 31 , 32 ]. Moreover, previous studies have demonstrated that a unique aroma and flavor was perceived in five AS species after roasting [ 8 ] and the aroma and flavor compounds may have been formed or released during roasting. However, the impact of roasting (180 °C) on AS may vary among the AS species due to the differences in their sizes and dimension.…”
Section: Resultsmentioning
confidence: 99%
“…AS is a good source of protein, dietary fibre, and minerals such as potassium, sodium, and iron [ 7 ]. The seeds are not consumed raw but are usually roasted mainly to develop a unique nutty flavour and aroma depending on the species and roasting conditions [ 7 , 8 ]. Moreover, roasting is carried out to reduce the anti-nutrients and protease inhibitors, particularly trypsin inhibitors in AS [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional value of A. retinodes seeds was also investigated, having being found with a different composition profile when compared with A. saligna seeds. Shelat et al [117] observed A. retinode seeds to contain a high protein (28%) and dietary fibre (34%) content and 16% of oil. The oil is characterized by 30% of saturated fatty acids, 53% of monounsaturated fatty acids and 18% of polyunsaturated fatty acids, with palmitic acid (18%), oleic acid (50%) and linoleic acid (16%) the most representative fatty acids [117].…”
Section: Nutritional Potential Of Seedsmentioning
confidence: 99%
“…The authors wish to make the following correction to the paper [ 1 ]: The title of Table 3 “Amino acid (g/100 g dry weight) profile of four different species of wattle seeds” should be changed to “Amino acid (mol% dry weight) profile of four different species of wattle seeds”. The title of first column in Table 5 “Sugar composition (%)” should be changed to “Sugar composition (mg/g biomass)”.…”
mentioning
confidence: 99%